Social research applied to English language teaching in Colombian contexts : theory and methods - Escobar Alméciga, Wilder Yesid (Editorial Universidad El Bosque, 2013)
"Within the diverse Colombian context, the issues concerning the teaching of English as a foreign language (EFL) call for theories and methodologies entering into the sociopolitical realms of influence which shape the dynamics of the language-acquisition process. As such [this book] takes into consideration a comprehensive analysis of five social phenomena, interpreting their impact, and prompting reflection on alternative strategies for development and growth within the EFL social environment ..."--Publisher's description.